Manifestations of the kitsch phenomenon in cemeteries: a brief essay on sentimentality, funerary art and death: Manifestations of the kitsch phenomenon in cemeteries: a brief essay on sentimentality, funerary art and death (Revista de História da UEG (REVHIST), 2021)
The bourgeoisie way of life inaugurates two important manifestations for this work: kitsch aesthetics and funerary pomp. From the mid-19th century onwards, both expressions became increasingly present in the day-to-day life of the Western culture. Here we present a problematization of the insertion of the kitsch phenomenon in cemeteries. We aim, in general, to analyze the changes and permanences in the sepulchral locus through the fads of funerary art and symbolic ensemble, until the appearance of funerary kitsch and the relationship of societies with cemeteries, expressed in the distance between being and death.Keywords: Cemetery. Kitsch. Sentimentalism.